Global and Local Persistence of Influenza A(H5N1) Virus - Li, Xianbin; Zhang, Zhong; Yu, Ailian; Ho, Simon Y. W.; Carr, Michael J.; Zheng, Weimin; Zhang, Yanzhou; Zhu, Chaodong; Lei, Fumin; Shi, Weifeng (Emerging infectious diseases, 2014)
An understanding of the global migration dynamics of highly pathogenic avian influenza A(H5N1) virus is helpful for surveillance and disease prevention. To characterize the migration network of this virus, we used genetic analysis, which supported a global persistence model in which each of 9 regions acts to some extent as a source. Siberia is the major hub for the dispersal of the virus. Southeast Asia and Africa are major sources of genetically and antigenically novel strains. We found evidence of local persistence of the virus in Southeast Asia and Africa, which is rare for human influenza A viruses. The differences in migration dynamics between avian and human influenza viruses might help with the design of region-specific surveillance efforts and the selection of vaccine candidates.